PENINGKATAN KINERJA INDUSTRI KECIL DAN MENENGAH MELALUI KONTRAK SUPPLY CHAIN - Evi Yuliawati; Anita Theresia (Universitas Muhammadiyah Ponorogo, 2017)
The contract is designed to manage the relationship between suppliers and retail. This coordination is needed in order to improve the performance of all actors in the supply chain including through savings in total cost. Small and Medium Industries (SMI/IKM), which maximizes to grow and evolve requires a culprit relationship management in order to compete in the marketplace. In this research, the implementation of buy-back contracts on IKMBatik Sidoarjo. The purpose of this study along with the purpose of implementation of the buy-back contracts is maximizing profits and their involved supply chain participants’ profits. This contract is done because IKM Batik Sidoarjo runs the mechanism where the retail is able to resell his or her goods amount at agreed price. The results showed that the implementation of the buy-back contracts for suppliers and retail on IKMBatik Sidoarjo are more profitable than ever before. This contract encourages retailers to buy products from suppliers in larger amounts at lower costs. Expectations of profit supplier, retail and supply chain increase along with the increase in the value of the repurchase.